Silver nanoparticles induce Egr‐1‐dependent psoriasin expression via the ERK and p38 pathways. (24th September 2018) - Kim, C. M.; Jeong, S. H.; Lee, H.; Ryu, H. J.; Son, S. W.
Summary: Background: Silver nanoparticles (Ag‐NPs) can prevent bacterial infection and improve cutaneous wound healing owing to their antimicrobial activity. However, the mechanism of their antimicrobial activity is poorly understood. Aim: To determine the mechanistic relationship between Ag‐NP treatment and expression of psoriasin. Methods: Human epidermal keratinocytes, neonatal (HEKn) were used. Psoriasin mRNA expression was measured by reverse transcription PCR and real‐time PCR. Western blotting was performed to verify expression of early growth response‐1 (Egr‐1) and psoriasin, and phosphorylation of mitogen‐activated protein kinase (MAPK). Psoriasin promoter activity by Egr‐1 was detected by a luciferase assay. Results: Treatment of HEKn with Ag‐NPs induced psoriasin mRNA and protein expression. Upregulation of psoriasin promoter activity was also observed in the luciferase assay. Ag‐NPs increased Egr‐1 expression, promoter activity and nuclear translocation in HEKn. Psoriasin luciferase activity was increased in HEKn transfected with Egr‐1 pcDNA 3.1. Ag‐NPs activated MAPK pathways including the extracellular signal‐regulated kinase (ERK), p38, and c‐Jun‐N‐terminal kinase (JNK) pathways. The upregulation of Egr‐1 expression by Ag‐NP stimulation was inhibited by ERK and p38 inhibitors, but not by a JNK inhibitor. Psoriasin expression was reduced in Egr‐1 small interfering RNA‐transfected HEKn. Conclusions: Ag‐NP treatment induces upregulation of psoriasin expression through Egr‐1 expression. We suggest that the ERK and p38 pathways are involved in Egr‐1‐dependent psoriasin expression.